1999
DOI: 10.1111/j.1469-7793.1999.0159r.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosinergic modulation of respiratory neurones in the neonatal rat brainstem in vitro

Abstract: Neuronal networks in the medulla oblongata generate respiratory rhythm in mammals. The pre-B otzinger complex (Smith et al. 1991) in the rostral ventrolateral medulla oblongata (RVL) (Onimaru et al. 1988) has been proposed to be the crucial site of this rhythmogenesis, but the detailed organization of this noed vitale is still unknown. The unique patterns of receptors and membrane channels expressed by specific types of neurones, and interaction between these neurones, maintains the central pattern generator f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 49 publications
3
53
1
Order By: Relevance
“…In respiratory networks, adenosine is clinically significant because it depresses ventilation (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999;Mironov et al, 1999), and is implicated in the hypoxia-induced depression of ventilation (Yan et al, 1995) and apnea in newborns (Runold et al, 1989;Lopes et al, 1994). Our observation that the post-ATP decrease in frequency depends on ATP breakdown suggests that effects of ATP on rhythm will be determined by an interaction between P2 and P1 receptors.…”
Section: Implication Of Atp Hydrolysismentioning
confidence: 88%
See 1 more Smart Citation
“…In respiratory networks, adenosine is clinically significant because it depresses ventilation (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999;Mironov et al, 1999), and is implicated in the hypoxia-induced depression of ventilation (Yan et al, 1995) and apnea in newborns (Runold et al, 1989;Lopes et al, 1994). Our observation that the post-ATP decrease in frequency depends on ATP breakdown suggests that effects of ATP on rhythm will be determined by an interaction between P2 and P1 receptors.…”
Section: Implication Of Atp Hydrolysismentioning
confidence: 88%
“…1 A). Given that extracellular ATP is rapidly hydrolyzed by ectonucleotidases to ADP and adenosine (Zimmermann, 2000(Zimmermann, , 2001, which is an inhibitory modulator of respiratory frequency (Herlenius et al, 1997;Herlenius and Lagercrantz, 1999), we tested whether the post-ATP inhibition of frequency results from the hydrolysis of ATP. We compared the effects on frequency of microinjecting into the preBötC ATP and ATP␥s, a nonhydrolysable analog of ATP.…”
Section: Receptor Subtypes Responsible For the Atp-induced Increase Omentioning
confidence: 99%
“…This in vivo response can be studied in the deafferented brainstem in vitro (24). It has been suggested that adenosine contributes to this depression by acting on brainstem neurons (25). This suggestion provides a rationale for the use of methylxanthines to reduce the number of neonatal apneas.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine, conversely, is an agonist at P1Rs in which the effect that has been primarily reported in fetal and neonatal animals to inhibit frequency through an A 1 R mechanism (Lagercrantz et al, 1984;Herlenius and Lagercrantz, 1999). Its effects, however, are confounded by possible actions at excitatory A 2a receptors, and developmental studies have yielded inconsistent results (Yamamoto et al, 1994;Kawai et al, 1995;Herlenius and Lagercrantz, 1999;Mironov et al, 1999;Brockhaus and Ballanyi, 2000;Wang et al, 2005;Mayer et al, 2006).…”
Section: Atp Byproducts Influence Rhythm and Atp Responses Perinatallymentioning
confidence: 99%
“…ADP is a P2YR agonist (Burnstock, 2006) and, therefore, could excite preBötC networks (Lorier et al, 2007). ADO is a P1R agonist whose actions are unclear, but, in premature and neonatal mammals, it is primarily reported to inhibit breathing (Herlenius et al, 1997(Herlenius et al, , 1999(Herlenius et al, , 2002. It is also implicated in apnea of prematurity (Bhatt-Mehta and Schumacher, 2003).…”
Section: Introductionmentioning
confidence: 99%